THE ROLE OF DARUL FALAH ISLAMIC BOARDING SCHOOL IN THE TRANSFORMATION OF ISLAMIC EDUCATION IN AEK SONGSONGAN - Agung Prasetyo; Laila Rohani (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines the role of Pesantren Darul Falah in transforming Islamic education in Aek Songsongan. The research uses a qualitative approach with a descriptive method to understand the changes in Islamic education within the local community after the establishment of the pesantren. Data were collected through interviews, observation, and documentation involving pesantren leaders, teachers, students, and community members. The results show that before the establishment of Pesantren Darul Falah, Islamic education in Aek Songsongan was still informal and not institutionally organized, mainly conducted through traditional Quranic learning and small religious gatherings. The presence of the pesantren brought significant changes by introducing a more structured and systematic educational system, improving religious understanding, and strengthening the moral and spiritual development of the community. In addition, the pesantren also contributed to increasing community participation in religious activities and improving achievements in religious competitions. Although the pesantren initially faced challenges related to public perceptions of the boarding school system, over time it gained trust and support from the community. Therefore, Pesantren Darul Falah plays an important role not only as an Islamic educational institution but also as an agent of educational and socio-religious transformation in Aek Songsongan.